Covering Islam : how the media and the experts determine how we see the rest of the world - Said, Edward W. (New York : Vintage Books, 1997)
"In this landmark work, for which he has written a new Introduction, one of our foremost public thinkers examines to origins and repercussions of the media's monolithic images of Islam. Combining political commentary with literary criticism, Edward Said reveals the hidden assumptions and distortions of fact that underlie even the most "objective" coverage of the Islamic world. In so doing, Covering Islam continues Said's lifelong investigation of the ways in which language not only describes but also defines political reality."--BOOK JACKET.
Ch. 1. Islam as News. I. Islam and the West. II. Communities of Interpretation. III. The Princess Episode in Context -- Ch. 2. The Iran Story. I. Holy War. II. The Loss of Iran -- III. Unexamined and Hidden Assumptions. IV. Another Country -- Ch. 3. Knowledge and Power. I. The Politics of Interpreting Islam: Orthodox and Antithetical Knowledge. II. Knowledge and Interpretation.
Includes bibliographical references and index.
Keywords: Islam -- Public opinion; Public opinion -- United States; Public opinion -- Europe